Інтелектуальна власність : робоча навчальна програма нормативної навчальної дисципліни - Лялюк, Алла Миколаївна; Lialiuk, A. N. (My University, 2013)
The program of the course. Content module 1. Rights in Intellectual Property. Content module 2. Economic relations in the field of intellectual property
Intellectual Property : Working curriculum
Keywords: Working curriculum; Intellectual Property; робоча програма; інтелектуальна власність